2017
DOI: 10.11604/pamj.supp.2017.27.3.12182
|View full text |Cite
|
Sign up to set email alerts
|

Immunization delivery in the second year of life in Ghana: the need for a multi-faceted approach

Abstract: Introductionin 2012, pneumococcal conjugate vaccine (PCV), rotavirus vaccine and a second dose of measles-containing vaccine (MCV2) were introduced into the Expanded Program on Immunization (EPI) in Ghana. According to Ghana’s EPI schedule, PCV and rotavirus vaccine are given in the first year of life and MCV2 in the second year of life (2YL) at 18 months. Although coverage with the last doses of PCV and rotavirus vaccine reached almost 90% coverage within four years of introduction, MCV2 coverage did not rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 5 publications
(5 reference statements)
0
24
0
Order By: Relevance
“…To collect CVAS module data, we designed and implemented a cross-sectional, household-based survey in Northern Region, Ghana. The primary intent of the survey was to estimate regional vaccination coverage as part of a multi-partner initiative to improve the coverage of childhood vaccinations in Ghana and is detailed elsewhere [19]; we incorporated our CVAS module into this survey. For the survey, we randomly selected 37 enumeration areas by probability proportional to size (PPS) sampling and then aimed to randomly select 10 households with children aged 12–35 months within each enumeration area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To collect CVAS module data, we designed and implemented a cross-sectional, household-based survey in Northern Region, Ghana. The primary intent of the survey was to estimate regional vaccination coverage as part of a multi-partner initiative to improve the coverage of childhood vaccinations in Ghana and is detailed elsewhere [19]; we incorporated our CVAS module into this survey. For the survey, we randomly selected 37 enumeration areas by probability proportional to size (PPS) sampling and then aimed to randomly select 10 households with children aged 12–35 months within each enumeration area.…”
Section: Methodsmentioning
confidence: 99%
“…However, challenges are noted around the timeliness of vaccinations received, with up to 60% of infants receiving delayed vaccinations [18], leading to survey items about the determinants of vaccination delay in Ghana. Additionally, the country has experience challenges with reaching high vaccination coverage for vaccines provided to children in their second year of life [19], with a recent study noting the need to implemented targeted strategies promoting parental behavior change to strengthen coverage of all vaccines recommended in in Ghana, regardless of age. Another study of human papillomavirus (HPV) vaccination uptake in Ghana identified challenges with low perceived risk of disease, role of the parents (as opposed to the provider or government) as the primary decision-makers for vaccination of the child, and parental concern about side effects following vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, about 70% of districts and regions have challenges with effective coverage of childhood immunization and a majority of children under-5 do not fully receive components of the child welfare services including immunization and growth monitoring (Bonsu, Senaya, Yawson, & Eleeza, 2017). A study conducted in Techiman to evaluate the immunization coverage among children older than 12 months revealed that, about 80% of children between 12-23 months were immunized, however, it was revealed that most of these children were partially immunized and a small number of children were not immunized at all (Adokiya et al, 2017).Patronage of child welfare clinic services including immunization of children and regular growth monitoring of children in Ghana has remained low (Nyaku, Wardle, Ametewee, Bonsu, & Opare, 2017). Statistics from the Ghana Health Service shows a consistent decline in the Child Welfare Clinic attendance and this decline has been attributed to knowledge gaps among caregivers, and a lack of defaulter tracing systems in most child welfare clinics (GHS, 2014).…”
Section: Introductionmentioning
confidence: 99%